The what and the how of self-care for sport psychology practitioners: A delphi study. Issue 6 (2nd November 2022) - Quartiroli, Alessandro; Wagstaff, Christopher R. D.; Thelwell, Richard
Abstract: Sport psychology professionals (SPPs) have recently noted the importance of engaging in self-care as means to an effective, ethical, and long-lasting career. Nevertheless, there currently exists no clear description of what self-care means to SPPs, the strategies they use, or how they experience these. As such, we sought consensual agreement from a panel of experts regarding a definition of self-care and perceived associated outcomes, as well as key self-care strategies, and any obstacles to enacting these experienced by SPPs. A multinational panel of twenty-three SPPs ( M = 13years experience, SD = 6.5) were invited to participate in a 3-round Delphi study. In round one, participants were invited to outline their personal definition of self-care. Following a content analysis of these answers, we developed a working definition of self-care and in subsequent rounds invited the panelists to rate the clarity, representativeness, importance, and easiness of adherence to this as an SPP. Furthermore, we sought consensus on the possible outcomes of self-care, such as enjoyment of life, positive professional quality of life, developing effective and ethical practice. Finally, participants were offered the opportunity to rate the frequency of challenges faced and strategies used to overcome them, as well as about the usefulness of the strategies and the level of challenge posed by each barrier. The implications for individuals and professional bodies are discussed in relation to professional development and training, wellbeing, and ethical and effective practice. Lay summary : Sport psychology professionals' (SPPs) self-care is key to an effective, ethical, and long-lasting career. In this study, a multinational group of SPPs consensually developed a working definition of self-care, identified its possible outcomes, and agreed upon the potential challenges hindering it, as well as the strategies to foster its. Applied implications: This work illustrates the importance of self-care activities being grounded in an individual's personal values and that self-care is most likely to develop as a result of deliberate engagement in activities aimed at prioritizing, developing, preserving, protecting, monitoring and restoring one's health, wellbeing, and life satisfaction. Professionals engage in self-care activities to experience a positive impact on their personal life and professional experience via the quality and effectiveness of their practice. It is important for trainees, with the support of their supervisors, to prioritize the development of self-care throughout their professional training to promote an early healthy and ethical approach to the profession.